Efeitos da administração central e periférica de ligantes dos receptores alfa2-adrenérgicos sobre as respostas de defesa induzidas por estimulação elétrica da matéria cinzenta periaquedutal dorsal de ratos - Muller, Cláudia Janaina Torres (2010)
Panic attacks are precipitated by the alpha2-adrenergic receptor antagonist yohimbine, but attenuated by the respective agonist clonidine. Defensive behaviors produced by eletrical stimulation of dorsal periaqueductal gray matter (DPAG) of rats have been proposed as a model of panic attacks. The DPAG projects to the locus coeruleus (LC). In turn, the LC projects to medial prefrontal cortex areas (CG1/CG2) which project to the DPAG, making up a midbrain-cortical circuit that may modulate the defensive behaviors. The LC also sends projections to DPAG. Therefore, this study examined the effects of the IO and CLO on the thresholds of defensive behaviors produced by eletrical stimulation of DPAG in four groups (n=20/group): 1) rats peripherally treated with IO (2, 5 and 10 mg/kg, i.p.); 2) rats peripherally treated with CLO (1, 2, 4 and 8 µg/kg, i.p.); 3) rats microinjected with IO into DPAG (0.28 nmol/150 nL, i.c.) and, 4) rats microinjected with IO into CG1/CG2 (0.07 nmol/150 nL, i.c.). Drugs were administrated in 48 h (i.p.) or 96 h (i.c.) intervals according to a balanced order. Drug and vehicle effects were compared through logistic regression. IO peripheral administrations facilitated immobility and trotting in the dose of 5 mg/kg, and galloping with 5 and 10 mg/kg. In turn, the peripheral administration of CLO attenuated jumping at higher doses (4 and 8 µg/kg), but facilitated defecation with 2 µg/kg. The microinjection of IO into the DPAG attenuated mostly the defecation, but also immobility and trotting. In contrast, micturition was facilitated the microinjection of IO into the DPAG. Microinjections of IO into CG1/CG2 attenuated the defecation and micturition 17 only. Peripheral effects of IO and CLO are a further validation of DPAG-based model of panic attack. Microinjections into DPAG or CG1/CG2 had variable effects on defecation and micturition, which not are typical components of panic attacks. Although the galloping was not affected, the microinjection of IO into DPAG attenuated immobility and trotting, which are most likely associated to anticipatory anxiety and panic attacks, respectively. The present results suggest that neither the facilitatory effects of IO, nor the attenuating effects of CLO on DPAG-evoked defensive responses are mediated by alpha2-adrenergic receptors in the DPAG and CG1/CG2.